Pentingnya Pengukuran dalam Penilaian Status Gizi dan Penerapan PHBS bagi Anak Usia 4-6 Tahun di TK Aisyiyah Bustanul Athfal 20 Denai - Amalia, Citra; Nurhidayah, Nurhidayah; Arifani, Toghur; Addina, Masyitah; Ulan, Widia (Lembaga Yasin AlSys, 2023)
This research aims to: 1). To find out how the nutritional status of children, 2). To implement PHBS that is suitable for children. This type of research is observational research with a descriptive approach. The subjects in this study were 30 children, consisting of 14 boys and 16 girls. The results of this study are that there are factors behind the subject having abnormal nutritional status including internal and external factors. Where internal factors consist of genetics, gender, infectious diseases, age, physical condition, and food intake. While the external factors consist of family, education, parents' work, culture, environment, physical activity, economy, and health services. Efforts to change people's behavior in order to support an increase in health status are carried out through the Clean and Healthy Behavior (PHBS) coaching program, especially for young children by being trained from an early age.